Building a better understanding of basic mechanical principles through analysis of the vertical jump - Reiser II, R. F.; Rocheford, E. C.; Armstrong, C. J. (Strength and Conditioning Journal, 2006)
An understanding of the basic mechanical principles governing movement is essential for the development of training programs, performance improvement, and injury prevention.The goal of this article is to review these principles through an analysis of the vertical jump. The vertical jump is a very common movement and simple in its goal to reach a point as high above the ground as possible. The key mechanical elements to success also are relatively straightforward: achieve the highest possible VCOM and PCOM at takeoff and then rearrange the body once in the air to position the reach hand as high above the COM as possible. However, to analyze a jump in further detail, a thorough understanding of the basic mechanical principles is necessary, not only to train a person to jump as high as possible, but also to prevent injury. Better understanding of the aforementioned mechanical principles will not only help strength and conditioning professionals in the training for and the analysis of the vertical jump, but other related movements as well.